Exploring The Effectiveness Of Mediation In Resolving Disputes In The Indonesian Administrative Court - Indriati Amarini; Noorfajri Ismail; Yusuf Saefudin; Zeehan Fuad Attamimi; Astika Nurul Hidayah (Journal & Publication Development Center Universitas Negeri Semarang, 2024)
Indexed by Scopus